INTRUISI LOGIKA PASAR KE DALAM PARTAI POLITIK - Andi Ali Said Akbar (Jurnal Ilmu Politik dan Pemerintahan, 2011)
Triggers weak performance and the morality of our politicians because of the presence of the business logic in the process of rooting kandidasi and political parties. Money seemed to be a single instrument to raise the party and gained a lot of voters. These frames influence the selection of the sources of political candidates and the quality of the bond with voters. It is also exacerbated by the political "hostages" in the election inspectors conducted by politicians for the sake of smooth stride play money in succession. Facts 2004 and 2009 elections show that the amount of money does not guarantee the competitiveness of candidates and political parties. Party is relatively new and limited pendanaanya able to compete and even overtake the party vote and affluent older funds. Because of that political parties and politicians should review the practice of politics in order to avoid the high cost of politics with disappointing results. To get there is important political party finance reform through the political revitalization of the party daily, diversify sources of financing political parties and strengthening the electoral watchdog.